The Influence of Social Media, Tourist Attraction and Price Perceptions on Visitors' Visitation Motivation and Decisions to Tanjung Lesung Sez - Devi Sri Bulan; Meylani Tuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
A factor that encourages tourists to visit tourist attractions is the price of the attractions, which is in line with what consumers anticipate, and the marketing of the attractions through social media. This study sought to ascertain the impact of social media, tourist allure, and pricing perceptions on travelers' motivation and choice to travel. As many as 152 persons were sampled using the incidental sampling technique. This investigation employs a structural equation model (SEM) with smart pls and a descriptive quantitative approach. The findings indicate that while visitor decisions to visit are unaffected, visitor incentive to visit is. While Social media influences visitors' motivation to visit but does not influence visitors' decisions to attend. Tourist. The results of this study have helped the administration of Tanjung Lesung SEZ to ramp up promotional activities so that more people are aware of the SEZ's existence and natural beauty, which would promote tourism. The local economy of the area around the tourist attraction will benefit from an increase in tourist numbers.